2001
DOI: 10.1007/pl00004238
|View full text |Cite
|
Sign up to set email alerts
|

Travelling Fronts and Entire Solutions¶of the Fisher-KPP Equation in ℝN

Abstract: This paper is devoted to time-global solutions of the Fisher-KPP equation in R N :It is well known that this equation admits a finite-dimensional manifold of planar travelling-fronts solutions. By considering the mixing of any density of travelling fronts, we prove the existence of an infinite-dimensional manifold of solutions. In particular, there are infinite-dimensional manifolds of (nonplanar) travelling fronts and radial solutions. Furthermore, up to an additional assumption, a given solution u can be rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
194
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(200 citation statements)
references
References 33 publications
(104 reference statements)
5
194
0
1
Order By: Relevance
“…Existence of smooth solutions of problem (1.1-1.2) with bistable nonlinearity f was obtained by Fife [16] for angles α < π/2 close to π/2. Conical-shaped and more general curved fronts also exist for the Fisher-KPP equation, with concave nonlinearity f (see [11], [21]). Other stability results were also obtained by Michelson [31] for Bunsen fronts solving the KuramotoSivashinsky equation, in some asymptotic regimes.…”
Section: Remark 18mentioning
confidence: 99%
“…Existence of smooth solutions of problem (1.1-1.2) with bistable nonlinearity f was obtained by Fife [16] for angles α < π/2 close to π/2. Conical-shaped and more general curved fronts also exist for the Fisher-KPP equation, with concave nonlinearity f (see [11], [21]). Other stability results were also obtained by Michelson [31] for Bunsen fronts solving the KuramotoSivashinsky equation, in some asymptotic regimes.…”
Section: Remark 18mentioning
confidence: 99%
“…Furthermore, Chen et al [9] considered entire solutions of reaction-diffusion equations with bistable nonlinearities for the case c = 0. Morita and Ninomiya [28] showed some novel entire solutions which are completely different from these observed in [8,16,20,21,22,47]. However, the above mentioned results are only concerned with entire solutions of reaction-diffusion equations in the absence of time delay and nonlocality.…”
Section: If H(x T) = δ(T)j(x)mentioning
confidence: 86%
“…On the other hand, it has been observed that traveling wave solutions are special examples of the so-called entire solutions that are defined in the whole space and for all time t ∈ R. In particular, Chen and Guo [8], Fukao et al [16], Guo and Morita [20], Hamel and Nadirashvili [21,22], Morita and Ninomiya [28] and Yagisita [47] have shown that the study of entire solutions is essential for a full understanding of the transient dynamics and the structure of the global attractors. These studies showed the great diversity of different types of entire solutions of reaction-diffusion equations in the absence of time delay.…”
Section: If H(x T) = δ(T)j(x)mentioning
confidence: 99%
See 1 more Smart Citation
“…− n (t; θ) := φ(−n + ct + θ), where θ varies in R (note that the wave speed c is unique in the bistable case). For reaction-diffusion equations with continuous spatial variables, Chen and Guo [14], Chen et al [15], Crooks and Tsai [20], Fukao et al [23], Guo and Morita [25], Hamel and Nadirashvili [26,27], Morita and Ninomiya [35] and Yagisita [50] showed the existence of new types of entire solutions other than the traveling wave type by using the well-known results of planar traveling wave solutions. As reported by Hamel and Nadirashvili [27, Theorems 1.7 and 1.8], reaction-diffusion equations usually have more types of entire solutions in high dimensional spatial spaces, which even includes some other classes of solutions of traveling wave type other than planar traveling waves.…”
Section: Introductionmentioning
confidence: 99%